(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Osteosarcoma is the most common primary bone tumor occurring in second and third decades of life with a second peak later. Biopsy (needle or incision) is necessary for diagnosis along with imaging modalities (X-ray, CT scan etc) and serology. Due to diagnostic dilemma in certain cases and for prognosis of patients, immunohistochemistry is increasingly used. Aims: To assess the pathologic features and determinants of osteosarcoma in patients of the Indian subcontinent that would put an insight into its appearance and behavior. Methods and Material: Forty cases of biopsy proven osteosarcoma were selected over a period of three years. Histopathology was done for tumor typing, along with serology (pre and post-operative serum alkaline phosphatase). In all cases TNM staging and immunohistochemistry for antibodies to Osteonectin (ON) (diagnosis), S100 (differentiation), Ki 67 and Her2 (prognosis) was done. Results: Serum alkaline phosphatase was high in 37 (92%) cases initially and remained high in metastatic and recurrent lesions. Osteonectin was positive in 38 (95%) cases, S100 in 31 (77%), Ki 67 showed overlapping labeling indices between 4.8-18.8% and Her2 showed more positivity in higher stage tumors. Conclusions: Biopsy (along with imaging) is mandatory to diagnose osteosarcoma. Osteonectin is a good immunohistochemical marker to differentiate osteosarcoma from its mimics. For prognostication, serum alkaline phosphatase, post chemotherapy tumor necrosis (more than 90%), lack of Her2 expression are good parameters. S100 and Ki67 were found to have limited role in diagnosis and prognosis of osteosarcoma. DOI: http://dx.doi.org/10.3329/bjms.v13i4.13573 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.443-448